Dyadic Interactions, Communication and Regulation Skills: Associations with Screen Use in Toddlers from Buenos Aires - Gago Galvagno, Lucas Gustavo (2024)
Background. Screen time has increased, with more frequent use at younger ages during the developmental process. International pediatric associations recommend that its use be minimal before three years of age. However, several studies have shown that in this age range, its use is for at least one hour per day, and in general without the accompaniment of an adult and with no consideration of age-appropriate content. Furthermore, negative associations between screen use in hours and minutes were reported with different cognitive abilities (e.g., language, executive functions, attention, memory) during this period. Many of the studies carried out on associations between these variables used questionnaires or parental reports. This is why it becomes important to study how screen time is associated with early interactions between primary caregiver and toddlers and with early cognitive skills, using measures that observe behavior directly, and in a non-WEIRD sample [a WEIRD population is White, Educated, Industrialized, Rich, and Democratic – ed.] from low-to-medium SES backgrounds in Latin America. This could generate interventions to promote early cognitive development, and evaluate what type of responsible use can be provided for screen consumption in the early years.Objective. To describe the use of screens in toddlers of low-to-medium SES, compare caregiver–toddler interactions when engaged in play with digital or physical stimuli (with screens or toys), and examine screen use associations with regulation, early communication skills, and sociodemographic variables.Design. A mixed quantitative research sample was of 33 dyads of low-to-medium-SES primary caregivers and toddlers from 12 to 36 months (M.age = 27.2 months, SD = 7.04, female = 16) from Buenos Aires, Argentina. Sociodemographic and screen use questionnaires, cognitive tasks of regulation and communication, and two free-play sessions of six minutes (i.e., with toys and screens) were used.Results. Caregivers reported that their toddlers were exposed to TV, background TV, and cell phones for more than one hour per day with different content types. Caregivers generally preferred toys to screens, had a negative view of screens, and reported using them to distract their toddlers. Play sessions with toys promoted more verbal and non-verbal interactions between caregivers and toddlers, and these interactions were positively related to cognition. Also, TV use had differential correlations with toddlers’ interactions depending on whether it involved verbal or non-verbal communication. Finally, negative associations of TV and background TV with cognitive and socioeconomic variables were found.Conclusion. It would be important to encourage participation in traditional games or other face-to-face interaction activities and develop interventions focused on parent education-related screen use, child development, and tips for engaging in quality interactions with toddlers.